Comparison of Soft and Hard Tissue Response between Screw Retained and Cement Retained Implant Prosthesis: An In-vivo Study - Haque, Merazul; Dable, Rajani Arun; Rao, Rayapati Srinivasa; Niranjan, Saurvi; Singh, Abanish; Singh, Harendra Mohan; Hussain, MD Asdaq (Med Phoenix, 2025)
Introduction: To mitigate the negative consequences of tooth loss, it's essential to consider tooth replacement. Implants have emerged as a leading treatment modality for effectively restoring lost dentition, meeting both functional and aesthetic demands with remarkable success. This study aimed to assess and compare the soft tissue and hard tissue responses around screw-retained and cement-retained implant prostheses. Materials and Methods: A prospective in vivo study was conducted, involving ten screw-retained and ten cement-retained implant prostheses placed in selected patients. Clinical parameters, including gingival bleeding index and marginal plaque index, were recorded. Radiographs were taken at 3, 6, and 9 months follow up to evaluate bone loss mesial and distal to each implant using ImageJ software. Statistical analysis was performed, and quantitative data were compared using the Kruskal-Wallis test. Results: Significant increases in the gingival bleeding index, marginal plaque index, and mean marginal bone loss were observed around both screw-retained and cement-retained prostheses throughout the study period. Conclusion: Although both retention types showed acceptable clinical performance over 9 months, statistically significant differences in soft and hard tissue responses suggest that clinical outcomes may be influenced by the type of prosthesis. Individual patient factors and clinical conditions should guide the choice of retention method.